Kegagalan Masuk Perguruan Tinggi Negeri Dalam Perspektif Islam Dan Sosial Kemasyarakatan - Imamul Arifin; Rosi Khunal Khayati; Nasywa Safira Arsyi Putri (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2021)
How to deal with failure and stay positive and not assume failure is the end of everything. For the purpose, namely how to overcome and prevent the impact of failure based on the Qur'an and how to change the view of the concept of failure based on the Qur'an and how to rise from failure by getting closer to Allah SWT. For the research method using Naturalistic research, namely on how to apply the science of the Qur'an in the perspective of Failing to Enter the Dream College.